The Effect of the “Course Review Horay” Cooperative Learning Model on the Mathematical Understanding of Fourth-Grade Students at Demakijo 1 Public Elementary School - Mahmuda Nur Dzaky; Fery Muhamad Firdaus (Eduvest - Journal of Universal Studies, 2026)
Mathematics learning in elementary schools often emphasizes procedural memorization rather than conceptual understanding, leading to students’ difficulties in grasping fundamental mathematical concepts such as multiplication and division. This condition highlights the need for innovative learning models that actively engage students and foster deeper understanding. This research aims to analyze the effect of the Course Review Horay cooperative learning model on the mathematical understanding of fourth-grade students at SD Negeri Demakijo 1 in multiplication and division material. This study uses a quantitative approach with a quasi-experimental design of a nonequivalent control group design. The research sample consisted of one experimental class treated with the Course Review Horay model and one control class using the Student Team Achievement Division (STAD) model, selected using a total sampling technique. Data were collected through a mathematical understanding test in the form of a pretest and posttest, then analyzed using a t-test after fulfilling the prerequisite tests for analysis. The results showed that the Course Review Horay model had a significant effect on students' mathematical understanding, with a significance value of 0.006 (< 0.05). This model is effective in improving students' abilities to explain concepts, connect mathematical ideas, and solve mathematical problems. The Course Review Horay cooperative learning model is effective in enhancing elementary school students' mathematical understanding. This model can serve as an alternative learning strategy to improve the quality of mathematics instruction, particularly in multiplication and division topics.